Palladium-catalyzed annulation and intermolecular hydroamination involving norbornene derivatives: synthesis of indanones and N -alkylamines - Li, Wenguang; Cheng, Xinfeng; Cao, Man; Sheng, Heyun; Gao, Wenchao; Chen, Ming; Zhang, Xu; Li, Wentao; Yu, Yongqi; Li, Ting (Chemical communications (Cambridge, England), 2024)
A palladium-catalyzed divergent reaction of primary benzamides using norbornene (NBE) derivatives as a controlled switch is reported. When NBE is used as a mediator, indanones are synthesized with moderate to good yields via a Catellani reaction that involves sequential ortho -C–H alkylation and ipso -C–N bond cleavage annulation of primary benzamides. Employing norbornadiene (NBD) instead of NBE enables the assembly of N -alkylamines by an intermolecular hydroamination reaction.